The Reasons Of Mistrust And Modification At Imamia - Ramadan Salman Qasim / Seyed Hasan Motehajjed Askari (Aale Mojjaddad) ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The objective of this research is to identify the trajectory of our scientists in how to diagnose narrators, distinguish confidences from them, adopt their own news, and know why the narrator diagnoses trust from others needs to be carefully tracked and studied in order to achieve the aim of documentation and weakness. Accordingly, we have come up with a statement of the reasons for mistrust and modification, and then a statement of the points of difference between the scientists of imamia from fundamentalists and informants in the legality of the uncertainty and then exposure to the issue of contradiction between them. We touched on the invalidity of the belief that there was no clear effect on men’s research as well as men of mistrust and modification at imamia.